Exploring nutrient intake and Mediterranean diet adherence across BMI categories in a Spanish adult population - Martin-Llaguno, Iciar; Saval-Calvo, Marcelo; Florez-Martin, Maria; Martin-Manchado, Laura; Zaragoza-Marti, Ana (Frontiers in Nutrition, 2025)
IntroductionObesity is often associated with excessive energy intake, yet individuals with obesity may also present with micronutrient inadequacies. This study examined dietary compliance and nutrient adequacy across Body Mass Index (BMI) categories in a sample of Spanish adults living in a Mediterranean context, and explored how adherence to the Mediterranean diet relates to BMI.MethodsA cross-sectional study was conducted between September 2020 and June 2021 among 167 adults classified as normal weight (n = 38), overweight (n = 47), or obese (n = 82). Participants meeting exclusion criteria such as pregnancy, endocrine disorders, or psychiatric illness were omitted. Dietary intake was assessed using a validated food frequency questionnaire specific to the Mediterranean population, complemented by 3-day dietary records. Nutrient adequacy was determined using European Food Safety Authority (EFSA) Dietary Reference Values, and adherence to the Mediterranean diet was measured with the 14-item MEDAS questionnaire.ResultsVitamin D and iodine inadequacy were highly prevalent across all BMI groups (96.41% and 74.85%, respectively). While unadjusted analyses suggested lower intakes of fiber, potassium, zinc, folate, and vitamins A, B1, C, and E in obese compared with normal-weight participants, these differences were not statistically significant after correction for multiple comparisons (false discovery rate q = 0.05). Small effect sizes (ε2 = 0.03–0.05) indicated consistent but modest trends toward lower micronutrient intake with increasing BMI. Average energy intake exceeded recommendations in all groups. Higher adherence to the Mediterranean diet was more common among normal-weight individuals and was inversely associated with BMI after adjusting for sex, educational level, labor status, physical activity, and energy intake.DiscussionIn this Mediterranean sample, obesity was not explained by total energy intake alone. Although differences in specific nutrient intakes did not remain statistically significant after adjustment, trends suggest lower dietary quality among individuals with obesity. Promoting nutrient-dense dietary patterns such as the Mediterranean diet may support healthier weight status.